Traditional uses, bioactive compounds and pharmacological uses of Vitex doniana Sweet: A Review - Mahmoud, Abdulrahman Dogara; S. Al-Rawi, Sawsan; A. Hama, Harmand (Ethnobotany Research and Applications, 2025)
Background: Medicinal plants have been extensively utilized and esteemed since ancient times for their multifaceted benefits. Owing to their Ethnopharmacological attributes, they become a vital reservoir for managing and averting ailments such as inflammation, coronary disease and cancer. Recently, Vitex doniana has garnered considerable interest for its possible therapeutic properties. The aim of the study is to provide a thorough and up-to-date review of published collection regarding the therapeutic properties, phytochemical composition, and pharmacognosy of V. doniana. Methods: Research articles were searched on Elsevier, Springer, Google Scholar, Taylor & Francis, PubMed, and Scopus using the keywords V. doniana, chemical composition, antioxidant, antibacterial, anti-diabetic, anticancer, and other relevant terms. Results: Vitex doniana was used in traditional medicine as a remedy for several health conditions including hypertension, paralysis, epilepsy, convulsions, spasm, sleeplessness, depression, and leprosy. Bioactive study revealed the presence of 483 compounds including hydroxycinnamic acid, saponin, allicin, flavonoids, terpenoid, aldehydes, amino acids, alkynes, alkane, hydrocarbon, phenethylamines, alcohol, and others. Most of these bioactive studies have focused on leaves. The medicinal and pharmacological capabilities have been substantiated by a diverse array of investigations, particularly highlighting its antioxidant, anti-inflammatory, antimicrobial, antibacterial, anti-diabetic, anti-epileptic, blood pressure regulating, hepatoprotective, anticancer, and anesthetic actions. Conclusions: It is crucial to ascertain its safe dosage and elucidate its mode of action. This offers potential for wider perceptions and advancement for a foundation for clinical investigations. This may garner attention for its efficacy as a supplement that promotes health and its potential for the development of novel herbal products. Keywords: Antioxidant, Africa, fruits, medicinal, plants, malaria, diabetes, and intestinal aliments, wounds, skin diseases, toothache fever, diarrhea and respiratory illnesses